The Religious Activities of Communities as a Learning Resource on Social Studies - Muhammad Ilmi; Syaharuddin Syaharuddin; Muhammad Rezky Noor Handy; Ersis Warmansyah Abbas; Mutiani Mutiani (The Innovation of Social Studies Journal, 2023)
The Pekauman lives a community living on the banks of the Martapura river with various activities, including a religious activity. Religious activities in Pekauman Village, Martapura, can be utilized in the learning process as a learning resource for social studies. The purpose of this research is to describe the religious activities of the riverbank community in Pekauman Village, Martapura, as a source of learning. Approach The research uses a qualitative approach with a descriptive method used by researchers. Research Location in Pekauman Village, Martapura. The research subjects were the Village Head (Pembakal) of Pekauman Village, the village elders of Pekauman Village, the local community of Pekauman Village, social studies subject teachers, and social studies lecturers. Data collection techniques by conducting observations, interviews, and documents. Data analysis techniques include data reduction, data presentation, and conclusions. Test the validity of the data used by using source triangulation. The results showed that religious activities in Pekauman Village, Martapura, were divided into 4, namely: daily, weekly, monthly, and yearly. Prayer activities, recitation, tahlilan and burdah, maulidan and donations, batamat Al-Quran, baarwahan, and bahaul, which these activities are used as the central axis and adhesive for community relations. These activities and activities are utilized as social studies learning resources, especially for classes VII and VIII related to social interaction material, social institutions, and the influence of social interaction (social mobility) on socio-cultural life, as well as Plurality (religion, culture, ethnicity, nation, occupation) of Indonesian society.